Associations en fusion(s). Penser les effets territoriaux des solidarités : crises des lieux, changements des liens - Emmanuel Bioteau; Jérôme Prugneau (Bulletin de l’Association de Géographes Français)
This text is based on two case studies: the merger of 9 Neighborhood (or community) centers associations approved as Social (or community) Centers into a single associative organization in La Roche-sur-Yon (AMAQY in Vendée, France) and the place and possible role played by associative Social Centers that were initially inter-communal but became communal within the framework of the communal mergers in the Mauges (in Maine-et-Loire, France). In these two situations, solidarity is presupposed. It would be the origin of all the mergers, based on a register of justification: the merger would "go without saying" because of a previous habit of "doing things together", between people used to "living together". However, the merger induces a change in values, a reallocation of these values, resistance, new alliances... which call into question solidarity, systematically invoked as a founding principle!